Gait analysis in patients with idiopathic scoliosis - Kramers-de Quervain, In sA; M ller, Roland; Stacoff, A.; Grob, Dieter; St ssi, Edgar (European spine journal, 2004)
The goal of this study was to observe scoliotic subjects during level walking to identify asymmetries--which may be related to a neurological dysfunction or the spinal deformity itself-and to correlate these to the severity of the scoliotic curve. We assessed the gait pattern of ten females (median age 14.4) with idiopathic scoliosis characterised by a left-lumbar and a right-thoracic curve component. Gait analysis consisted of 3D kinematic (VICON) and kinetic (Kistler force plates) measurements. The 3D-segment positions of the head, trunk and pelvis, as well as the individual joint angles of the upper and lower extremities, were computed during walking and static standing. Calculation of pertinent kinetic and kinematic parameters allowed statistical comparison. All subjects walked at a normal velocity (median: 1.22 m/s; range:1.08-1.30 m/s; height-adjusted velocity: 0.75 m/s; range: 0.62-0.88 m/s). The timing of the individual gait phases was normal and symmetrical for the whole group. Sagittal plane hip, knee and ankle motion followed a physiological pattern. Significant asymmetry was observed in the trunk's rotational behaviour in the transverse plane. During gait, the pelvis and the head rotated symmetrically to the line of progression, whereas trunk rotation was asymmetric, with increased relative forward rotation of the right upper body in relation to the pelvis. This produced a torsional offset to the line of progression. Minimal torsion (at right heel strike) measured: median 1.0 degree (range: 5.1 degrees -8.3 degrees), and maximal torsion (at left heel strike) measured 11.4 degrees (range 6.9 degrees -17.9 degrees). The magnitude of the torsional offset during gait correlated to the severity of the thoracic deformity and to the standing posture, whereas the range of the rotational movement was not affected by the severity of the deformity. The ground reaction forces revealed a significant asymmetry of [Msz], the free rotational moment around the vertical axis going through the point of equivalent force application. On the right side, the initial endo-rotational moment was lower, followed by a higher exo-rotational moment than on the left. All the other force parameters (vertical, medio-lateral, anterior-posterior), did not show a significant side difference for the whole group. The use of a brace stiffened torsional motion. However the torsional offset and the asymmetry of the free rotational moment remained unchanged. The most significant and marked asymmetry was seen in the transverse plane, denoted as a torsional offset of the upper trunk in relation to the symmetrically rotating pelvis. This motion pattern was reflected by a ground-reaction-force asymmetry of the free rotational moment. Further studies are needed to investigate whether this behaviour is solely an expression of the structural deformity or whether it could enhance the progression of the torsional deformity.